2014
DOI: 10.1002/nmi2.55
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of Coxiella burnetii Dog Utad, a strain isolated from a dog-related outbreak of Q fever

Abstract: Coxiella burnetii Dog Utad, with a 2 008 938 bp genome is a strain isolated from a parturient dog responsible for a human familial outbreak of acute Q fever in Nova Scotia, Canada. Its genotype, determined by multispacer typing, is 21; the only one found in Canada that includes Q212, which causes endocarditis. Only 107 single nucleotide polymorphisms and 16 INDELs differed from Q212, suggesting a recent clonal radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In these countries some hyperendemic foci also can be identified, as in Martigues, a city in southeastern France, where the Q fever incidence rate reaches 34.5/100,000 inhabitants due to dissemination of spores by the local mistral wind from sheep herds breeding in the local plains (46). Small outbreaks (especially familial outbreaks) may occur after exposure to a common source, such as C. burnetiiinfected parturient pets such as dogs or cats (47,48). Also, an anecdotal outbreak was recently reported in the United States in five patients, due to intramuscular injection of fetal sheep cells by a German doctor practicing "live cell therapy," a xenotransplantation practice with no published evidence of efficacy (49).…”
Section: Epidemiological Characteristics Of C Burnetii Infection Ovementioning
confidence: 99%
See 2 more Smart Citations
“…In these countries some hyperendemic foci also can be identified, as in Martigues, a city in southeastern France, where the Q fever incidence rate reaches 34.5/100,000 inhabitants due to dissemination of spores by the local mistral wind from sheep herds breeding in the local plains (46). Small outbreaks (especially familial outbreaks) may occur after exposure to a common source, such as C. burnetiiinfected parturient pets such as dogs or cats (47,48). Also, an anecdotal outbreak was recently reported in the United States in five patients, due to intramuscular injection of fetal sheep cells by a German doctor practicing "live cell therapy," a xenotransplantation practice with no published evidence of efficacy (49).…”
Section: Epidemiological Characteristics Of C Burnetii Infection Ovementioning
confidence: 99%
“…Since 2003, six new whole genomes of C. burnetii have become available in GenBank (142)(143)(144). Sixteen incomplete genomes can also be found (27,47,(145)(146)(147)(148)(149)(150). In 2009, Beare et al performed a comparative genomic analysis of four strains and found a total of 125 pseudogenes, of which 65 were highly conserved, and 8 IS families (142).…”
Section: Comparative Genomics and Pangenomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with C. burnetii in humans is usually asymptomatic but it may trigger acute and chronic clinical manifestations. C. burnetii is also one of main pathogens causing reproductive losses in livestock ( 1 ) and reproductive failure in pets ( 2 , 3 ) and wildlife ( 4 7 ). Clinical signs of Q fever in domestic ruminants are diverse; it has been associated with sporadic cases of abortion, premature delivery, stillbirth, and weak offspring in cattle, sheep, and goats, but epidemics with increased reproductive failure have been reported for sheep and goats mainly ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 In canine species, the epidemiological role of C. burnetii infection is still debated; however, seropositivity has been reported in dogs, and human outbreaks associated with parturient bitches have been described. 13,14 C. burnetii DNA has also been recently detected in 4 of 54 canine placentas originating from aborting animals in The Netherlands. 15 Leptospirosis is a worldwide re-emerging disease caused by a gram-negative bacterium of the genus Leptospira.…”
Section: Introductionmentioning
confidence: 99%